Study on Spatial Adaptability of Tangjia Village in the Weibei Loess Plateau Gully Region Based on Diverse Social Relationships - Qin He; Guochen Zhang; Jizhe Zhou; Xintong Zhao; Ruiqi Dong; Quanhua Hou (Land)
In the context of rapid urbanization, traditional villages in the Weibei Loess Plateau gully region are facing compounded pressures from social structure disruption and physical space reconstruction. It is urgent to deeply analyze the influence mechanism of social relations on spatial adaptability. This study attempts to construct an analytical framework that couples social relationships with village spatial development. With Tangjia Village in the gully region of the Weibei Loess Plateau as an example, the study integrated various data sources such as satellite imagery, interviews, and policy documents. Through social network analysis and an improved cascade failure model, the spatial adaptation processes and characteristics based on changes in kinship, occupational ties, and geographical networks were explored. The findings indicate that (1) before 2001, kinship networks led to the formation of a monocentric settlement structure. From 2001 to 2011, occupational ties fostered the differentiation of industrial and residential zones. After 2011, geographical networks drove the multifunctional integration of space. (2) Clan-based settlement zones (consisting of 80 kinship nodes) and core cultural tourism facilities are key units in maintaining spatial adaptability. The research reveals the impact mechanism of social network fission on spatial function reorganization and proposes adaptive planning strategies, aiming to provide theoretical and practical value for the coordinated governance of society and space in traditional villages.